In vitro function of cyst epithelium from human polycystic kidney. - Perrone, R D (The Journal of Clinical Investigation, 1985)
It is thought that cysts in polycystic kidneys originate from nephron segments and function in a manner similar to the segment or origin. The indirect evidence for this derives from studies of microanatomy and cyst fluid composition. Cysts with low Na+ have been classified as distal, whereas cysts with high Na+ have been classified as proximal. In order to directly determine the transport characteristics of cyst epithelium, cysts from a human polycystic kidney were studied in vitro using Ussing chamber techniques. Composition of cyst fluid was determined in parallel with these studies. Cysts with low Na+ (gradient cysts) demonstrate characteristics consistent with distal nephron origin including elevated potential difference (PD), short-circuit current (Isc), and low conductance. PD and Isc of gradient cysts were amiloride sensitive. Nongradient cysts, however, require additional characterization. At least two types of nongradient cysts were identified, one with characteristics consistent with proximal nephron origin and another apparently without function. These studies are the first direct evidence for active transport of cysts from human polycystic kidney and provide strong evidence to support the concept that cysts function in the same manner as the nephron segment of origin.